2022
DOI: 10.1128/spectrum.01396-22
|View full text |Cite
|
Sign up to set email alerts
|

Colicins of Escherichia coli Lead to Resistance against the Diarrhea-Causing Pathogen Enterotoxigenic E. coli in Pigs

Abstract: This study revealed the heterogeneity of E. coli strains from pigs, including two strains studied by both in silico and wet experiments in detail and 14 strains studied by bioinformatics analysis. E. coli Y18J may improve the adaptability of pigs toward disease resistance through the production of colicins B and M. Our findings could shed light on the pathogenic and harmless roles of E. coli in modern animal husband… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…With the rapid progress of sequencing techniques, more and more high-quality metagenomic sequencing of genetic resources in complex microbial communities has been completed [ 32 ], which is analogous to genome library construction and screening [ 33 ]. Through the mining of gene sequencing information in the past decades, a large number of reagents composed of enzymes [ 33 ], small peptides [ 34 ], and secondary metabolites [ 35 , 36 , 37 ] have been discovered and applied in industry, medicine, and agriculture. Here, we revealed the natural products from metagenomic sequencing in the pig gut.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid progress of sequencing techniques, more and more high-quality metagenomic sequencing of genetic resources in complex microbial communities has been completed [ 32 ], which is analogous to genome library construction and screening [ 33 ]. Through the mining of gene sequencing information in the past decades, a large number of reagents composed of enzymes [ 33 ], small peptides [ 34 ], and secondary metabolites [ 35 , 36 , 37 ] have been discovered and applied in industry, medicine, and agriculture. Here, we revealed the natural products from metagenomic sequencing in the pig gut.…”
Section: Discussionmentioning
confidence: 99%
“…These BGCs are generally organized into multiple operon modules within genomes, which work together as assembly lines to tailor metabolic products [ 40 ]. In inter- and intraspecies interactions, natural products participate in biofilm inhibition [ 41 ], stress protection [ 42 ], and the killing of competitors [ 37 ]. To address the threat from multiple-resistant bacteria, molecules with growth-inhibitory activities have aroused the specific interest of researchers and may serve as precursors to the lead compounds of new antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Contigs were circularized using Circlator [ 31 ]. The assembled genome was annotated to identify the protein-coding and RNA genes using the National Center for Biotechnology Information (NCBI) Prokaryotic Genome Annotation Pipeline [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…In an attempt to find a suitable native promoter, we used the pNGS-mNeoNGreen vector for fluorescence ex-pression intensity analysis. 40 Flow cytometry analysis showed that the expression intensity of P CHA0D was the highest (Figure 4). Therefore, we selected P CHA0D as the target promoter and proceeded to construct a promoter library.…”
Section: Nitrogen Fixation Gene Cluster Analysis Of Vnmentioning
confidence: 99%